No evidence of sibling cooperation in the absence of parental care in Nicrophorus vespilloides. (1st December 2018) - Magneville, Camille; Ratz, Tom; Richardson, Jon; Smiseth, Per T.
Abstract: Interactions among siblings fall on a continuum with competition and cooperation at opposite ends of the spectrum. Prior work on the burying beetle Nicrophorus vespilloides suggests that parental care shifts the balance between competition and cooperation by masking a density‐dependent shift from cooperation to competition. However, these results should be interpreted with caution because they were based on correlational evidence for an association between larval density at dispersal and mean larval mass at dispersal. Here, we test for a causal effect of the initial density of larvae in a brood on the larvae's subsequent performance in the absence of care. We find no effect of the initial larval density on mean larval mass. Thus, our results provide no evidence for sibling cooperation in the absence of care in this species. However, using larval density at dispersal as a predictor of mean larval mass at dispersal, there was a significant correlation between larval density and mean larval mass. Our study highlights the importance of using experimental designs that exclude confounding effects due to shared environmental conditions that otherwise could be misinterpreted as evidence for sibling cooperation.